PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SDN 146/VIII REJOSARI KABUPATEN TEBO - Dwi Novri Asmara; Nopi Wulandari; Martiya Nurni Khairita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Education is an effort to foster and develop human personality both spiritually and physically. Education also develops one's talents to the optimum level within the limits of the nature of the individual, with the aim that every human being can participate in the development of Man and society continuously to achieve more dignity of life. The problems that become the background in this study is the low learning outcomes of Mathematics class IV SDN 146 / VIII Rejosari Tebo. Efforts to overcome this is to apply the Make A Match learning model in mathematics learning. This study uses the type of research Quasy Experimental Design. The population in this study is all students in SDN 146 / VIII and the sample is two rombel Class IV amounted to 50 students with a total of 25 people from each class. Data collection techniques taken using pretest and posttest sheets are calculated and compared based on criteria and analyzed by normality test, homogeneity test and hypothesis test through SPSS 20 at the level of 0.05. While the data collection techniques taken using test sheets and then analyzed also using normality test, homogeneity test and hypothesis test through SPSS 20 at the level of 0.05. The results of data analysis of the hypothesis test on the independent sample t test with a significance level of 0.05 shows the results of GIS. (2-tailed) is smaller than then Ho is rejected. While the results of the analysis of test data from the hypothesis test on the independent sample t test with a significance level of 0.05 shows the results of GIS. (2 tailed) is smaller than then Ho is rejected. Based on the analysis of observational data and test data, it can be concluded that the make a match learning model has a significant influence on the learning outcomes of Mathematics Fourth Grade Elementary School.